Digital Competence, Leadership Agility, and Employee well-being as Drivers of Public Service Administration Effectiveness: The Mediating Role of Organizational Citizenship Behavior - Samsuddin, Samsuddin; Amang, Baso; Nujum, Syamsu; Selong, Abbas (International Review of Management and Marketing, 2026)
This study aims to identify and analyze the influence of digital competence, leadership agility, and employee well-being on Organizational Citizenship Behavior (OCB) and the effectiveness of public service administration. The influence of Organizational Citizenship Behavior (OCB) on the effectiveness of public service administration, as well as the influence of digital competence, leadership agility, and employee well-being on the effectiveness of public service administration at the Banjarmasin Class I Port Authority and Harbor Master’s Office, is mediated by Organizational Citizenship Behavior (OCB). This study employs a quantitative research approach, with a sample of 130 employees from the Banjarmasin Class I Port Authority. Data analysis techniques include descriptive analysis, validity and reliability testing, and SEM using Amos. Digital competence has a positive and significant effect on Organizational Citizenship Behavior (OCB). Leadership agility has a positive and significant effect on organizational citizenship behavior. Employee well-being has a positive and significant effect on organizational citizenship behavior. Digital competence does not have a significant direct effect on the effectiveness of public service administration. Leadership agility has a positive and significant effect on the effectiveness of public service administration. Employee well-being has a positive and significant effect on the effectiveness of public service administration. Organizational Citizenship Behavior (OCB) has a positive and significant effect on the effectiveness of public service administration. Organizational Citizenship Behavior (OCB) mediates the effect of digital competence on the effectiveness of public service administration. Organizational Citizenship Behavior (OCB) partially mediates the effect of leadership agility on the effectiveness of public service administration. Organizational Citizenship Behavior (OCB) also partially mediates the effect of employee well-being on the effectiveness of public service administration.